Tendecias del formato “Noticias en desarrollo” en los medios de comunicación digital del cantón Vinces - Zúñiga Bajaña, Julissa (2021)
The arrival of the internet has generated multiple advantages within the different fields, especially in communication and journalism, where the appearance of various digital platforms has been useful and beneficial for society in general due to its speed and easy access to them. In the same way, various traditional media have been forced to evolve their information methods and immerse themselves in the digital world. However, despite the positive things that have arisen with digitization, certain shortcomings have also become noticeable within some native media that often fall into the error of not developing or structuring those journalistic reports within these virtual spaces, which has caused a great dissatisfaction on the part of each of its users. This is how currently these websites have given rise to a new trend known as "news in development", the same one that does not have a good writing and that leaves many empty questions, this is because some digital media choose forever wanting to have the premise of certain information and therefore, they launch their news without prior inquiry.